The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1073/pnas.1508093112
|View full text |Cite|
|
Sign up to set email alerts
|

Discontinuity in the genetic and environmental causes of the intellectual disability spectrum

Abstract: SignificanceIntellectual disability (ID) is present in almost 3% of children and fundamentally characterized by IQ scores below 70. Genetic research has shown that it is among the most heritable traits, and it has been accepted that ID is the extreme low of the normal IQ distribution. However, we show that, while the genetic and environmental factors influencing mild ID (lowest 3% of IQ distribution) are similar to those influencing IQ in the normal range, factors influencing severe ID (lowest 0.5%) differ fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 48 publications
(63 reference statements)
12
68
1
2
Order By: Relevance
“…Interestingly, findings were different for the most severe form of ID (profound ID) which did not show familial co-aggregation with ADHD. This finding is in keeping with the view that ID mainly lies at one end of a multi-factorial, polygenic continuum of intellectual ability whereas profound ID is etiologically distinct and qualitatively different from the rest of the IQ spectrum and mild-moderate ID 7 . This discontinuity appears to apply to the familial co-aggregation with ADHD and might be explained by rare causes including genetic syndromes (e.g.…”
supporting
confidence: 88%
“…Interestingly, findings were different for the most severe form of ID (profound ID) which did not show familial co-aggregation with ADHD. This finding is in keeping with the view that ID mainly lies at one end of a multi-factorial, polygenic continuum of intellectual ability whereas profound ID is etiologically distinct and qualitatively different from the rest of the IQ spectrum and mild-moderate ID 7 . This discontinuity appears to apply to the familial co-aggregation with ADHD and might be explained by rare causes including genetic syndromes (e.g.…”
supporting
confidence: 88%
“…Family studies yield high heritability estimates in ASD (Yip et al, 2018), but comparable 6 estimates of heritability in severe NDD are lower (Reichenberg et al, 2016). Consistent with 7 these observations, exome studies identify a higher frequency of disruptive de novo variants in 8 severe NDD than in ASD (Deciphering Developmental Disorders, 2017).…”
Section: Relationship Of Asd Genes With Gwas Signal 18mentioning
confidence: 80%
“…While genome-wide studies using microarrays and exome sequencing have identified a prominent role of de novo copy number variations (CNVs), INDELs and single nucleotide variants in mostly severe ID with reported diagnostic yields of 13%-42%, their role in mild ID is less studied but expected to have a less prominent role 3,4 . Intriguingly siblings of mild ID individuals have low IQ compared to the general population whereas the IQ of siblings of severe ID individuals do not differ from the general population 5 . This suggests that mild ID represents a low extreme in a normal distribution of IQ, while severe ID is a distinct condition with different etiology 5 .…”
Section: Introductionmentioning
confidence: 87%